ANALISIS FENOMENA WORKAHOLISM DALAM PERSPEKTIF AL-QUR’AN: Kajian Tematik Berdasarkan Tafsir Al-Mishbah - Inas Syafiqah; Hana Natasya (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
Phenomenon that describes workers who work beyond the demands and normal working hours or workaholism leads to various health problems, both physically and mentally. This article aims to examine the phenomenon of workaholism and its solutions from the perspective of the Qur’an, using the interpretation of Tafsir al-Mishbah. This research is based on library studies and analysis from various other sources. The findings of this research indicate that in the Qur’an, Allah SWT commands His servants to seek sustenance through work, but also provides a limitation not to overdo it. As a solution, the Qur’an explains the importance of living in balance, which in this context can be understood as balancing work with rest to avoid the negative impacts of workaholism. This also proves that the Qur’an serves as a guide for human life, providing solutions to human problems throughout all times, supported by interpretations (tafsir) that continue to evolve across generations